ANALISIS PRAGMATIK TERHADAP PENGGUNAAN INTERJEKSI PENANDA IMPRESI TERKEJUT DALAM KOMIK DETEKTIF CONAN KARYA AOYAMA GŌSHŌ - Kurniawati, Rianita; Mulya, Komara; Rismorlita, Cut Erra (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2020)
There are many types of interjection in Japanese, one of which is a marker of the impression of surprise expressed differently depending on the conditions behind it. The purpose of this study is to examine the use of kandou no kandoushi marker of surprise impressions in the comic Detective Conan vol. 70 of Aoyama Gosho's works are seen from pragmatic reviews. This research uses descriptive method and literature study that is by describing a situation / actual phenomenon in daily life and by conducting a review of books relating to analysis. The results showed that there were seven kandou no kandoushi markers of surprise impressions contained in the detective conan comic vol.70. The Kandoushi include e ’, ee, a, nani, wa’, are, and ara. The conclusion of this study is that each of the no-kandoushi kandou has different functions and uses because the context behind them is also different. The various functions found in each kandoushi cannot replace the position of one kandoushi with another.